Analisis Pengaruh Budaya Perusahaan “Akhlak”, Kepuasan Kerja, Dan Gaya Kepemimpinan Terhadap Motivasi Kerja Dan Kinerja Karyawan (Studi Kasus Pada Pt Permodalan Nasional Madani Pusat) - Sisyanto, Rahardian Tri Nugroho; Suharto, Eduardus (Jurnal Sosial Teknologi, 2025)
This study aims to determine the effect of Corporate Culture "Akhlak", Job Satisfaction, and Leadership Style on Work Motivation and Employee Performance at PT. Permodalan Nasional Madani Pusat. With quantitative methods, with a total of 195 respondents and analyzed using Smart PLS. This study provides results that H1 is accepted so it can be concluded that there is a positive and significant influence between Organizational Culture "AKHLAK" on Work Motivation, H2 is accepted so it can be concluded that there is a positive and significant influence between Job Satisfaction on Work Motivation, H3 is accepted so it can be concluded that there is an influence between Leadership Style on Work Motivation, H4 is accepted so it can be concluded that there is a positive and significant influence between Organizational Culture "AKHLAK" on employee performance, H5 is accepted so it can be concluded that there is an influence of Job Satisfaction on employee performance, H6 is accepted so it can be concluded that there is a positive and significant influence between Leadership Style on employee performance, H7 is accepted so it can be concluded that there is a positive and significant influence between Work Motivation on employee performance at PT. Permodalan Nasional Madani Pusat.